Spesifikasi Kertas Karton Gelombang (KKG) Untuk Nanas Kaleng - Wiwik Pudjiastuti (Jurnal Kimia dan Kemasan, 1995)
Corrugated boxes as secondary packaging can decrease the damage of the primary packaging during transportation process. Experiment has been carried out to determine spesification of corrugated boxes canning pineapple. From physical and transportation test of corrugated board and boxes showed that the spesification of corrugated boxes for canning pineapple were Regular Sloted Container (RSC) type 0201, inner dimension 351 x 175 x 355 mm with corrugated board aimed at "Standar National Indonesia" (SNI) 14 - 1439 - 1989.